The Acquisition of English Prepositions in Descriptive Text Written by Indonesian EFL Learners (a case study of X-grade students at SMA 17 Agustus 1945 Surabaya in the academic year of 2025): Akuisisi Preposisi Bahasa Inggris dalam Teks Deskriptif yang Ditulis oleh Pembelajar Bahasa Inggris sebagai Bahasa Asing (EFL) Indonesia (studi kasus siswa kelas X di SMA 17 Agustus 1945 Surabaya pada tahun ajaran 2025) - Abdillah, Mega; Pariyanto (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
Abstract. This study aims to analyze the extent of preposition use in descriptive texts written by English as a foreign language (EFL) learners in Indonesia. The method used is descriptive text analysis. Data were collected from 28 EFL students of grade 10 at SMA 17 Agustus 1945 Surabaya in the academic year of 2025 in the descriptive texts they wrote. The results showed significant variation in the ability to use English prepositions accurately in their descriptive texts. Of the total 419 prepositions used, 369 were used correctly and 50 were used incorrectly. Individual student scores varied between 60 as the lowest score to 100 as the highest score, with ten students achieving perfect accuracy without errors. Meanwhile, several other students still experienced difficulties, indicated by a high number of errors in the use of certain prepositions. The average overall preposition mastery score was 88.52%, indicating that the majority of students had a fairly good understanding, although there were still some confusing preposition forms or certain contexts. This variation is likely influenced by first language (L1) interference, the level of English exposure in the learning environment, and each student's learning habits. These findings confirm that EFL students' mastery of prepositions is at a good level, but there is still a need to improve the quality of input and more targeted practice to achieve a more comprehensive understanding.